The Effect of (K.W.L) Based Instructional Program on Developing Critical Reading Skills for the 1st Secondary Students and their Attitudes towards it - Feras M Al Slaiti (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aimed at investigating the effect of (K.W.L) based instructional program in developing critical reading skills and the 1st secondary students' attitudes towards  it in Jordan. To achieve this result, the researcher designed a functionally-based instructional program, and a test consisting of (16) multiple choice items to measure the creative levels in reading, and students' attitudes towards creative reading consisting of (18) of Likert scale items.The sample of the study was (123) students from Irbid first educational directorate (al koora) of the academic years 2015-2016. They were chosen purposively: (61) of them represented the experimental group and the other (62) represented the control group. The results of the study revealed that there were statistically significant differences in the critical reading level due to the way of teaching, also in favor of the experimental group (Instructional program). Results showed no significant differences in the critical reading skills due to gender or interaction between the program and gender. There were statistically significant differences in the students' attitudes toward critical reading due to the effect of the program, and in favor of the experimental group. The results also revealed statistically significant differences in the attitudes of students towards critical reading due to gender (male, female) for female students. The researcher suggested that further researches should be conducted on the effectiveness of K.W.L strategy on different language skills and in developing positive attitudes towards reading.